Stability and solubility improvement of Sompoi (Acacia concinna Linn.) pod extract by topical microemulsion - Worrapan Poomanee (2018)
© 2017 Shenyang Pharmaceutical University The aim of this study was to enhance the solubility and stability of Acacia concinna extract by loading in a microemulsion for topical application. Both physical appearance and biological activities of the extract-loaded microemulsion were determined in comparison with the extract solution. Pseudoternary phase diagrams of three oil types including tea seed oil, grape seed oil, and sesame oil, together with polysorbate 85 or the mixture of polysorbate 85 and sorbitan oleate as surfactants, and absolute ethanol as a co-surfactant were constructed to optimize the microemulsion area. The selected microemulsion was then characterized for droplet size, polydispersity index, and viscosity. Tea seed oil exhibited the highest microemulsion area in the phase diagram because it had the highest unsaturated fatty acid content. The microemulsion composed of tea seed oil (5%), polysorbate 85 (40%), ethanol (20%), and water (35%) exhibited Newtonian flow behavior with the droplet size and polydispersity index of 68.03 ± 1.09 nm and 0.44 ± 0.04, respectively. After 4% w/w of the extract was incorporated into the microemulsion, larger droplets size was observed (239.77 ± 12.69 nm) with a lower polydispersity index (0.37 ± 0.02). After storage in various conditions, both physical appearances and the stability of biological activity of the extract-loaded microemulsion were improved compared to the solution. Therefore, the A. concinna loaded microemulsion may be a promising carrier for further development into a topical formulation and clinical trials for pharmaceutical and cosmeceutical applications are also suggested.